Assessment of photodegradation of the sodium salt of iminoglutamic succinic acid and the ecotoxicity of its decomposition products - Pronovich Nataliya; Khlebova Daria; Kamalova Alina; Khamieva Aliya; Khamiev Marsel (E3S Web of Conferences)
The article analyzes the intensity of photodegradation of the sodium salt of a new synthesized chelating agent, a potential "environmentally friendly" alternative to the well–known chelating agent ethylenediaminetetraacetic acid - iminoglutamic succinic acid, as well as the toxicity of its photodegradation products. Ethylenediaminetetraacetic acid, like many other chelating agents used as a base for micronutrients in agriculture, has a number of disadvantages, including low biodegradation and slow photodegradation in the environment. The new synthesized substance, iminoglutamic succinic acid, is a possible alternative to the chelates used due to its fertilizing properties and higher degree of biodegradation. For a broader understanding of the behavior of IGSA in natural systems, as a component of micronutrients, and the effect of this substance on non-target biota, a photodegradation experiment with two types of water (distilled and lake) was performed under the following parameters: an illumination of 2500 lux, stirring at 60 rpm, and a temperature of 24 oC. As a result of the experiment, it was found that the photodegradation intensity of this substance ranged from 5 to 18%, the absence of toxicity of photodegradation products in relation to Paramecium caudatum, low toxicity in relation to Ceriodaphnia affinis (EC10 varied from 12 to 35 g/l) was established, in addition, photodegradation products stimulated the growth of microalgae Chlorella vulgaris up to 235%. It has been established that photodegradation products are not toxic for hydrobionts, however, they can cause eutrophication of reservoirs.